Uncovering the molecular mechanisms between heart failure and end-stage renal disease via a bioinformatics study - Bian, Rutao; Xu, Xuegong; Li, Weiyu (Frontiers in Genetics, 2023)
Background Heart Failure (HF) is not only a common complication in patients with end stage renal disease (ESRD), but also a major cause of death. Although clinical studies have shown that there’s a close relationship between, but the mechanism of its occurrence is unclear. The aim of this study was to explore the molecular mechanisms between HF and ESRD through comprehensive bioinformatics analysis, providing a new perspective on the crosstalk between these two diseases. Methods The HF and ESRD datasets were downloaded from Gene Expression Omnibus (GEO), identified common differentially expressed genes (DEGs) by analysis. The Gene Ontology (GO), Kyoto Encyclopedia of Genes and Genomes (KEGG), Gene set enrichment analysis (GSEA) and Gene set variation analysis (GSVA) were applied to explore potential biological functions and construct Protein-Protein Interaction (PPI) networks. Also, four algorithms Random forest (RF), Boruta algorithm, Logical regression of the selection operator (LASSO) and Support vector machine-recursive feature elimination (SVM-RFE) were used in HF and ESRD datasets respectively to clarify the hub genes. CIBERSORT was used to analyze the immune cell infiltration in HF patients. Target miRNAs and Transcription Factors (TFs) were identified using miRTarBase and CheA3 databases, respectively, and Cytoscape software was applied to construct mRNA-miRNA-TFs regulatory networks. Finally, the drug Signatures database (DSigDB) database was used to identify potential drug candidates. Results A total of 68 common DEGs were identified. The results of the enrichment analysis suggest that immune response and inflammatory factors may be common features of HF and ESRD pathophysiology. Four hub genes (BCL6, CCL5, CNN1, PCNT) were validation. Immune infiltration analysis showed that immune cells such as macrophages, neutrophils, and NK cells were altered in HF myocardial tissue, while neutrophils were significantly correlated with all four hub genes. In addition, 10 TFs and 25 target miRNAs were obtained and 10 gene-targeted drugs were discovered. Conclusion Our study revealed important crosstalk between HF and ESRD. These common pathways and pivotal genes may provide new ideas for further clinical treatment and experimental studies.